Shear strength behavior of clayey soil reinforced with polypropylene fibers under drained and undrained conditions - Correia, N. S. (2021)
The fundamental mechanisms controlling shear strength and deformability behavior of clay-fiber mixtures have still not been well established, nor the constraints that may affect their performance of shearing under different drainage conditions. This study aims to understand the behavior of a clay soil mixed with polypropylene fibers using results from drained and undrained triaxial compression tests, and to provide necessary calibration data for a shear strength prediction model. In drained tests, shear strength increased with fiber inclusion for a given mean effective stress, represented by an increase in apparent cohesion. In the undrained tests, the shear strength was not affected by pore water pressure generation. Results from the drained and undrained tests indicate that the fiber content had a greater influence on the apparent cohesion than on the friction angle. Drainage affected the improvement in the peak shear strength of fiber-reinforced soils, with superior improvement in the drained tests. As the percent improvement in shear strength decreased with increasing effective confining stresses for both tests, the difference in behavior in the drained and undrained tests was attributed to the strain at failure, with failure occurring at large strains in the drained tests but at smaller strains in the undrained tests.